PREDICTING THE EFFICIENCY OF PHYSICAL THERAPY OF PNEUMONIA PATIENTS WITH CORONAVIRUS DISEASE DURING REHABILITATION STAGES - Korota, Yu. V.; Nekhanevych, O. B.; Lohvynenko, V. V. (Rehabilitation and Recreation, 2024)
The aim is to develop a predictive model for the effectiveness of physical therapy in improving cardiorespiratory endurance in patients with pneumonia during the rehabilitation stages of COVID-19. Material. During the hospitalization phase, 42 patients with coronavirus disease were enrolled in the study. Patients were randomly allocated into the main (n=21) and control (n=21) groups. The physical therapy program for the main group included stretching exercises for upper limb, chest, and trunk muscles. Additionally, all patients in the main group were assigned exercises focused on normalizing breathing, irrespective of the presence of productive cough and/or moist rales. All patients underwent questionnaires, anthropometry, assessment of weakness and cough severity, upper limb muscle strength, balance, and cardiorespiratory endurance. In the long-term rehabilitation stage, the study included 30 patients. Patients performed the physical rehabilitation program individually or in groups of 3–4 individuals, five days a week for six weeks after discharge. All patients underwent questionnaires, anthropometry, assessment of quality of life, cardiorespiratory endurance, lung involvement degree evaluation, and quantitative analysis of the transforming growth factor β1 (TGF-β1). The results. The most significant factors predicting improvement in the 6-minute walk test at the end of the stationary rehabilitation phase were the scores of the “Up and Go” test (regression coefficient B=-4.1) and the strength of the non-dominant upper limb muscles (B=2.3). The developed model predicts outcomes within 14% of existing values, indicating satisfactory performance (determination coefficient 42%). In the long term, at 6 weeks, 6 months, and 12 months, the levels of C-reactive protein (B=-0.34, B=-0.4, and B=-0.3, respectively), transforming growth factor β (B=-0.76, B=-0.73, and B=-0.72, respectively) in serum, and the level of physical functioning according to the SF-36 questionnaire (B=1.46, B=0.72, and B=0.85, respectively) were significant. The developed models predict outcomes within 6%, 19%, 21%, respectively (determination coefficient 76%, 62%, 60%, respectively), indicating satisfactory and effective performance. Conclusions. On the post-acute rehabilitation stage, the most significant indicators for predicting the restoration of cardiorespiratory endurance were the strength of the non-dominant upper limb muscles and the balance test scores, while during the long-term rehabilitation period, the levels of TGF-β and CRP in the serum of patients during the illness were key indicators.